Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0046690
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic Findings in Peruvian Patients with Chronic Diarrhea

Abstract: ObjectiveTo report the colonoscopic and pathological findings in patients with chronic diarrhea from a gastroenterology unit during approximately 3 years in a general teaching hospital located in Lima-Peru.Materials and MethodsPatients with chronic diarrhea as the motive for colonoscopy from March 2008 to December 2010 were selected from the colonoscopy report computerized database. Colonoscopic findings were registered. Biopsies taken during the procedure were prospectively reviewed.Results226 patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(15 reference statements)
4
4
0
Order By: Relevance
“…This observation indicates that colonoscopy is a safe procedure done in all age groups and can be biopsied for further evaluation. The sex and age incidence were in concordance with studies done by Shah et al 11 & Galvez V J et al 3 All the 100 cases were presented with diarrhea (bloody and non-bloody) along with other coexisting symptoms like pain abdomen (37%), weight loss (24%) and fatigue (8%), while the study done by Shah et al 11 showed associated findings like pain abdomen (43%), weight loss (9%), rectal bleeding (27%) and anaemia (15%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation indicates that colonoscopy is a safe procedure done in all age groups and can be biopsied for further evaluation. The sex and age incidence were in concordance with studies done by Shah et al 11 & Galvez V J et al 3 All the 100 cases were presented with diarrhea (bloody and non-bloody) along with other coexisting symptoms like pain abdomen (37%), weight loss (24%) and fatigue (8%), while the study done by Shah et al 11 showed associated findings like pain abdomen (43%), weight loss (9%), rectal bleeding (27%) and anaemia (15%).…”
Section: Discussionsupporting
confidence: 91%
“…The present study reported 12 cases as tuberculosis commonest granulomatous lesion in India having male to female ratio of 2:1 mostly occurring at 40-60 years age group. The findings are akin to the studies done by Villa fuerte G J et al 3 Pulimood A et al 15 and Kirsch R et al 16 Ulcerative colitis though rare is emerging disease in India this condition portrays remission and relapses. In the present study, 9 cases of UC were diagnosed with a male to female ratio of 2:1 and occurring at the age group of 20-40 years which are comparable to done by Deroche et al, 17 Shah et al 11 described 7 cases of ulcerative colitis in their colonoscopic study of 168 cases.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Summary of evidence: The frequency of MC in patients with chronic or intermittent watery diarrhoea and a macroscopically normal (or near normal) colon has been evaluated in several studies 17 ,. 18 , 21 , 26 , 27 , 42–72 Based on studies with a moderate or high quality, and a sample size of ≥100 patients, 17,18,21,26,27,42,43,45–47,49,52,54,56,59,60 the pooled overall frequency of MC was estimated to be 12.8% (95% CI: 9.9–15.9, I 2 = 93.6%). The pooled frequency of CC and LC was 4.96% (95% CI: 3.6–6.5, I 2 = 85.2%) 17,18,21,26,27,42,43,45,47,49,52,54,56,60 and 8.2% (95% CI: 6.0–10.8, I 2 = 92.0%), 17,18,21,26,27,42,43,45,47,49,52,54,56,60 respectively (see also Supporting Information Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 9 ] Despite the use of invasive colonoscopy in chronic diarrhea, the majority of macroscopic findings are unremarkable. [ 10 ] The most common causes include irritable bowel syndrome, IBD, microscopic colitis, and malabsorption syndromes. [ 11 ] Infection is an uncommon cause of chronic diarrhea.…”
Section: Introductionmentioning
confidence: 99%